2014
DOI: 10.1177/0148607114545995
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Alkaline Phosphatase in Infants With Parenteral Nutrition–Associated Liver Disease Reflects Bone Rather Than Liver Disease

Abstract: While elevated ALP can reflect biliary stasis, the ALP elevation observed in infants with IF and PNALD is predominantly of bone rather than hepatic origin. An elevated unfractionated ALP in infants with PNALD should therefore raise suspicion of underlying bone disease, rather than being attributed to liver disease alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…Regular measurements of urinary calcium, plasma calcium, phosphorus, parathyroid hormone and 25-OH vitamin D concentrations and serum alkaline phosphatase activity should be performed as part of the evaluation of MBD in patients on PN. Elevated serum alkaline phosphatase activity in infants on PN indicates bone rather than hepatic origin [116] (LOE 3). Diagnosis of bone disease relies primarily on the measurement of bone mineralization using validated imaging methods (e.g.…”
Section: Osmolaritymentioning
confidence: 99%
“…Regular measurements of urinary calcium, plasma calcium, phosphorus, parathyroid hormone and 25-OH vitamin D concentrations and serum alkaline phosphatase activity should be performed as part of the evaluation of MBD in patients on PN. Elevated serum alkaline phosphatase activity in infants on PN indicates bone rather than hepatic origin [116] (LOE 3). Diagnosis of bone disease relies primarily on the measurement of bone mineralization using validated imaging methods (e.g.…”
Section: Osmolaritymentioning
confidence: 99%
“…Thus, an elevated ALP in infants with IF can therefore reflect DILI (as IFALD) or MBD. In a recent article by Nandivada et al, the authors performed a retrospective review of patient data of infants diagnosed with IFALD and demonstrated that although an elevated ALP could be due to IFALD alone, the high ALP often seen in this population was actually due to occult MBD. In that study, bone‐derived ALP comprised a mean of 80.9% of total ALP.…”
Section: Discussionmentioning
confidence: 99%
“…Adult criteria for DILI included 1 or more of (a) ≥5× ULN for ALT, (b) ≥3× ULN for ALT and >2× ULN for TB, or (c) ≥2× ULN for ALP. Since prior research has shown ALP may be a nonspecific marker of liver disease, we also investigated GGT, a hepatic marker not included in the current DILI criteria, in lieu of ALP . A conservative GGT ≥1× ULN threshold was selected for this investigation to determine if any sort of conclusion could be made knowing that in cases of severe end‐stage liver failure, GGT levels will actually decrease rather than rise .…”
Section: Methodsmentioning
confidence: 99%
“…El origen es multifactorial, en el que influyen tanto la enfermedad de base como mecanismos relacionados con la NP: deficiencia de vitamina D, desequilibrio en los aportes de fósforo, nitrógeno y energía, exceso de aminoácidos y contaminación con aluminio, entre otros. Una revisión reciente sugiere que los aumentos en los niveles de fosfatasa alcalina que se ven con frecuencia en NP en lactantes son de causa ósea y no hepática en la mayoría de ocasiones (36).…”
Section: Enfermedad Metabólica óSea (Osteoporosis Osteomalacia)unclassified